Pengelolaan Eksternalitas Lingkungan dalam Sektor Pariwisata Melalui Penerapan Green Economy di Indonesia - Esta Azzahra; Aji Ali Akbar (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In the era of globalization and rapid technological development, sustainable development has become crucial for a country's growth, especially in the tourism sector, which has significant potential to drive economic growth and environmental conservation. This research aims to examine how environmental externalities from the tourism sector can be effectively managed through the application of green economy principles. The method used is a qualitative approach with literature study, which includes analysis of the concept of green economy, the impact of tourism on society, and policies that can internalize negative impacts. The research results indicate that the application of green economy principles can reduce negative externalities caused by tourism, such as pollution and ecosystem damage, while also improving the welfare of local communities. Policies such as Pigovian taxes, subsidies, and regulations are necessary to support this implementation. Therefore, sustainable tourism management through green economy not only focuses on economic profit but also on environmental and social sustainability.